Efektivitas Pembelajaran IPS Berbasis ICT Melalui TVRI Di Tengah Pandemi Covid-19 - Taseman; Arikah Mayari; Durroh Nasihatul Ummah; Badriatul Hasanah (Fakultas Tarbiah Institut Agama Islam (IAI) Hamzanwadi Pancor, 2021)
Learning Social Sciences (IPS) in Madrasah Ibtidaiyah is a process of delivery by educators about the social sciences combined with education of students in a learning environment. Information and Communication Technologies (ICT) based learning is used to carry out social studies learning processes to be more effective. During the covid-19 pandemic the government advocated teaching and learning from home by watching broadcasts of learning material from TVRI television channel. This research uses descriptive analysis method with data collection techniques through Google Forms questionnaire and interview activities conducted online. Research subjects are students, teachers, and parents. The purpose of this study was to determine the effectiveness of social studies learning through television broadcasts on TVRI channels during the Covid-19. The results showed that ICT-based learning presented through TVRI was less effective in applying it to elementary / MI students because the material was global and not appropriate with curriculum goals and the majority of students could understand the material presented optimally